Subject Index (Journal of the American College of Cardiology, 2015)
Category Type Presentation Numbers Page Numbers Acute Coronary Syndrome: STEMI, NSTE-ACS Oral A-004 - 020 S2 - S10 Acute Coronary Syndrome: STEMI, NSTE-ACS Poster A-125 - 134 S63 - S66 Acute Coronary Syndrome: STEMI, NSTE-ACS Cases C-001 - 031, C-227 S83 - S131 Adjunctive Procedures: Thrombectomy, Plaque Modification, Others Oral A-021 S10 Adjunctive Procedures: Thrombectomy, Plaque Modification, Others Poster A-135 S66 Adjunctive Procedures: Thrombectomy, Plaque Modification, Others Cases C-032 - 040 S132 - S144 Antiplatelet Agents and Anticoagulants LBCT A-001 S1 Antiplatelet Agents and Anticoagulants Oral A-022 - 025, A-136 S10 - S11 Antiplatelet Agents and Anticoagulants Poster A-137 S67 Antiplatelet Agents and Anticoagulants Cases C-041 S144 - S146 Basic Science, Animal Models and Preclinical Studies Oral A-026 - 029 S12 - S13 Basic Science, Animal Models and Preclinical Studies Poster A-138 - 142 S67 - S68 Bifurcation and Left Main Stenting Oral A-030 - 040, A-143 S14 - S20 Bifurcation and Left Main Stenting Poster A-144 S68 - S69 Bifurcation and Left Main Stenting Cases C-042 - 067, C-228 S146 - S188 Carotid & Neurovascular Intervention Cases C-068 - 071 S189 - S194 Cell Therapy and Angiogenesis Oral A-041 S20 - S21 Cell Therapy and Angiogenesis Poster A-145 S69 Chronic Total Occlusions Oral A-042 - 048 S21 - S26 Chronic Total Occlusions Cases C-072 - 109, C-229, C-230 S195 - S261 Complex Oral A-049, A-050 S27 - S28 Complex Poster A-146, A-147 S69 - S71 Complex Cases C-110 - 130 S262 - S302 Congenital Heart Disease Oral A-051 - 055 S29 - S31 Congenital Heart Disease Cases C-131 - 134, C-232 S302 - S312 Drug-eluting Stents LBCT A-002 S1 Drug-eluting Stents Oral A-056 - 064 S31 - S34 Drug-eluting Stents Poster A-148 - 152 S71 - S72 Drug-eluting Stents Cases C-135 - 137 S312 - S317 High Risk Patients: Diabetes, Heart Failure, Renal Failure, Others Oral A-065 - 072 S34 - S38 High Risk Patients: Diabetes, Heart Failure, Renal Failure, Others Poster A-153 - 158 S73 - S75 High Risk Patients: Diabetes, Heart Failure, Renal Failure, Others Cases C-138 - 144 S317 - S327 Hypertrophic Obstructive Cardiomyopathy Oral A-073 S38 Hypertrophic Obstructive Cardiomyopathy Cases C-145 S328 - S330 Innovative Devices and Futuristic Therapies Oral A-074, A-075 S38 - S39 Invasive Coronary Imaging: IVUS, OCT, Spectroscopy, and Other LBCT A-003 S1 Invasive Coronary Imaging: IVUS, OCT, Spectroscopy, and Other Oral A-076 - 083 S39 - S43 Invasive Coronary Imaging: IVUS, OCT, Spectroscopy, and Other Poster A-159 S75 Invasive Coronary Imaging: IVUS, OCT, Spectroscopy, and Other Cases C-146 - 156 S330 - S348 Non-Invasive Cardiac Imaging: CTA, MRI, 3D-Echo, and Other Oral A-084, A-085 S43 - S44 Non-Invasive Cardiac Imaging: CTA, MRI, 3D-Echo, and Other Poster A-160 - 162 S75 - S76 Non-Invasive Cardiac Imaging: CTA, MRI, 3D-Echo, and Other Cases C-157 S348 Other (Unclassified) Oral A-086 - 092 S45 - S49 Other (Unclassified) Poster A-163 - 166 S76 - S77 Other (Unclassified) Cases C-233, C-158, C-159 S349 - S354 Other Pharmacologic Agents Oral A-093, A-095, A-096 S49 - S50 Other Pharmacologic Agents Poster A-167, A-094 S77-S78 Peripheral Vascular Intervention (Non-carotid, Non-neurovascular) Oral A-097 - 106 S50 - S56 Peripheral Vascular Intervention (Non-carotid, Non-neurovascular) Poster A-168 - 175 S78 - S80 Peripheral Vascular Intervention (Non-carotid, Non-neurovascular) Cases C-160 - 210, C-231 S355 - S439 Physiologic Lesion Assessment Oral A-107 - 111 S56 - S58 Physiologic Lesion Assessment Cases C-211 - 215 S440 - S448 Structural Heart Disease, Other Poster A-176 S80 Structural Heart Disease, Other Cases C-216 - 218 S448 - S455 Transradial Intervention Oral A-112 - 115 S58 - S59 Transradial Intervention Poster A-177, A-178 S80 - S81 Transradial Intervention Cases C-219 - 221 S455 - S461 Valvular Heart Disease Oral A-116 - 123 S60 - S62 Valvular Heart Disease Poster A-179 - 182 S81 - S82 Valvular Heart Disease Cases C-222 - 226 S461 - S469 Vulnerable Plaque Diagnosis and Treatment Oral A-124 S62